Optimizing the Solubility of Fat-Soluble Vitamins: A Study on Vitamin K2 Dissolution in Various Oils (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Vitamin K2 (menaquinone) is a fat-soluble vitamin crucial for bone health, cardiovascular function, and calcium metabolism. However, its bioavailability is significantly influenced by the medium in which it is dissolved. This study explores the solubility of Vitamin K2 in various oils, examining the physicochemical properties that affect dissolution rates and stability. By analyzing different carrier oils such as medium-chain triglycerides (MCT), olive oil, sunflower oil, and fish oil, this research provides insights into optimizing Vitamin K2 delivery for enhanced absorption and efficacy. The study further discusses the implications of oil selection in pharmaceutical formulations and functional food applications.